Revealing the Critical Factor in Metal Sulfide Anode Performance in Sodium‐Ion Batteries: An Investigation of Polysulfide Shuttling Issues. Issue 1 (11th November 2019) - Hu, Mingxiang; Ju, Zhengyu; Bai, Zhongchao; Yu, Kang; Fang, Zhiwei; Lv, Ruitao; Yu, Guihua
Abstract: Metal sulfides are a class of promising anodes for sodium‐ion batteries with high theoretical capacities. However, the properties of intrinsic metal sulfide anodes usually decay rapidly at initial cycling of batteries. Previously, it was believed that the low conductivity and volume expansion of metal sulfides lead to the poor performance. Here, using in situ batteries followed by the assistance of spectral analysis, it is shown that the polysulfide shuttling effect is one of the crucial factors for the degradation of metal sulfide anodes beyond traditional consensus of low conductivity and volume expansion. Furthermore, a novel strategy by controlling the dissolution of sodium polysulfides in selected electrolyte is proposed to enable intrinsic metal sulfides to work stably in polysulfide‐insoluble fluoroethylene carbonate electrolyte, which would decay fast in polysulfide‐soluble propylene carbonate electrolyte. This work has deepened the understanding of electrochemical reaction mechanisms of metal sulfide anodes and expanded the strategies to optimize the electrochemical performance of metal sulfides anodes. Abstract : Metal sulfide anodes have high theoretical capacities for sodium‐ion batteries. Here, the polysulfide shuttling effect is identified as one of the crucial factors for the performance degradation beyond traditional consensus of low‐conductivity and volume‐expansion issues of metal sulfides. Fluoroethylene carbonate (FEC)‐based electrolyte is proposed to greatly enhance the electrochemical properties of metal sulfide anodes.